Characterization of grains and panicles quality of Cuban sorghum cultivars harvested at two grain vegetative stages and two harvesting season - Rodríguez-Mendieta, Janhad L.; Gil-Díaz, V. D.; Marrero-Suárez, L. I.; Castro-Alegría, A.; Hoedtke, Sandra; Lima-Orozco, R. (Cuban Journal of Agricultural Science, 2016)
The effect of harvesting season (HS: rainy vs. dry) and grain vegetative stage (GVS: soft dough vs. hard dough) at harvesting time on grains and panicles quality parameters from three sorghum (Sorghum bicolor (L. Moench)) cultivars (new cultivar: CIAP MC-04-12, subsp. bicolor, race guinea; commercial cultivars: CIAP 2E-95 and CIAP 132R-05, subsp. bicolor, race bicolor) during two years (2011 and 2012) were determined. The GVS at harvesting time affected all studied parameters, while HS at harvesting time affected the dry matter, crude protein (CP), neutral detergent fiber, the slowly digestible starch fraction, organic matter (OM) digestibility and digestible energy (DE). The starch (St) of the new sorghum cultivar was classified as a St of slow digestibility and showed lower proportion of highly digestible St fraction as compared with the commercial sorghum cultivars. The hard dough grains showed the best nutritive value independent of HS (e.g., new sorghum cultivar: 127-130 g CP/kg DM, 673-677 g St/kg DM, 867-884 g digested OM/kg DM and 14.6- 14.9 MJ DE/kg DM). In this study grains from new sorghum cultivar have good nutritional value to pigs and provide a basis for further studies as an interesting animal feed alternative, especially for non-ruminants. Key words: sorghum, grain vegetative stage, nutritive value, grain quality, starch